Recovering the Barbarians: Reprinting “Forgotten Fantasy” in the 1970s - Cowan, Yuri (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherche et d’étude sur le livre au Québec, 2010)
In the 1960s and 70s, a new interest in the prehistory of fantastic literature found its paperback and digest magazine form in projects of textual recovery like the Ballantine Adult Fantasy series, Forgotten Fantasy Magazine, and the Newcastle Forgotten Fantasy series. This article describes how the material form of these books speaks to their intended audience of fans of science fiction and fantasy, and compares the processes of editing and disseminating Victorian fantasy to the social practices of SF fandom. In the colourful covers and facsimile reprints of these reprints the exigencies of cheap dissemination and the desire to make the works accessible to a modern audience result in eclectic, modern paratexts under the guidance of editors such as Doug Menville, Robert Reginald, and Lin Carter, themselves active readers who form, collect, and print their own personalized bodies of essential fantasy literature, blurring the arbitrary boundaries between author, reader, editor, publisher, and fan.